2013
DOI: 10.3406/paleo.2013.5493
|View full text |Cite
|
Sign up to set email alerts
|

The South-Eastern Jordan’s Chalcolithic – Early Bronze Age Pastoral Nomadic Complex : Patterns of Mobility and Interaction

Abstract: Dès les recherches entreprises au début des années 1980 dans le sud jordanien, en particulier dans le secteur compris entre Aqaba et Ma’an, un mode d’occupation basé sur le pastoralisme nomade a pu être mis en évidence pour les périodes du Chalcolithique et du Bronze ancien. L’image reflétée par cette extension de l’occupation “ timnienne” contraste avec celle du peuplement des zones agricoles sédentaires. Les données récentes fournies par l’étude micro-régionale du secteur de al-Thulaythuwat, ainsi que celles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…They are represented by large aggregations of multiple stone enclosure units that almost systematically include internal subdivisions as well as vast courtyards. The nature of this outstanding form of occupation has been discussed elsewhere; it seems to be restricted to the southern arid margins of Jordan and is thought to reflect a high pastoral component of the Late Prehistoric occupation (Abu‐Azizeh , ). Its dating is still subject to question, but one radiocarbon date is available from a similar site investigated during a previous stage of our research, suggesting that it could be attributed to the beginning of the fourth millennium BC (calibrated), a Late Chalcolithic/Early Bronze Age transitional time frame (Abu‐Azizeh : 368; site TH.126: 3968–3800 cal.…”
Section: Discussion: J Al‐khashabiyeh and J Al‐ghadiwiyat Kites In mentioning
confidence: 99%
See 1 more Smart Citation
“…They are represented by large aggregations of multiple stone enclosure units that almost systematically include internal subdivisions as well as vast courtyards. The nature of this outstanding form of occupation has been discussed elsewhere; it seems to be restricted to the southern arid margins of Jordan and is thought to reflect a high pastoral component of the Late Prehistoric occupation (Abu‐Azizeh , ). Its dating is still subject to question, but one radiocarbon date is available from a similar site investigated during a previous stage of our research, suggesting that it could be attributed to the beginning of the fourth millennium BC (calibrated), a Late Chalcolithic/Early Bronze Age transitional time frame (Abu‐Azizeh : 368; site TH.126: 3968–3800 cal.…”
Section: Discussion: J Al‐khashabiyeh and J Al‐ghadiwiyat Kites In mentioning
confidence: 99%
“…These pastoral nomadic campsites are composed of a variable number of stone enclosures, ranging from one up to ten units. Although the simple stone enclosures, with or without compartments, represent the majority, the double ‘cell and fence’ as well as complex subdivided units are well represented (for a description of pastoral nomadic stone enclosure typology, see Abu‐Azizeh , , , ). Although the surface material collected from these sites during survey was quite limited, the recurrence of cortical scrapers among the few identified diagnostic artefacts was characteristic.…”
Section: Discussion: J Al‐khashabiyeh and J Al‐ghadiwiyat Kites In mentioning
confidence: 99%
“…The term 'pastoralist' holds many levels of meaning, and while the essence of this term relates to the 'foundation of the management of domesticated animals' (Rollefson et al 2014 and references therein), the origins of such pastoral societies and the question of their socioeconomic independence is of major importance. Following a model suggesting that their origins are in PN societies in the Mediterranean zone (Gopher 2012(Gopher : 1570(Gopher -1575, it was suggested that alongside with an economy based on animal herding, those nomad populations were also involved in additional subsistence activities (see Gopher 2012Gopher : 1570Gopher -1575 e.g., the production and exchange of beads, procurement of raw material and production of tabular scrapers and later, possibly even activities related to the metal industry (Rosen 1983;1997: 75;Quintero et al 2002;Wright & Garrard 2003;Müller-Neuhof 2006;Fujii 2011;Klimscha 2011;Abu-Azizeh 2013;Milevski 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Timnian groups followed a central-based wandering settlement pattern of transhumance in which their cyclical migrations appear to have been seasonally governed by the availability of water and pasturage (Abu-Azizeh, 2013;Henry, 1994Henry, , 1995. Dependent upon the differences in elevational amplitude of the landscape encompassed within their annual range, groups made either relative short, vertical or longer, horizontal transhumant migrations.…”
Section: Anthropogenic Forces: Emergent Market Economy and Populationmentioning
confidence: 99%